A new treatment for coconut fibers to improve the properties of cement-based composites – Combined effect of natural latex/pozzolanic materials - Silva, Everton Jose da; Marques, Maria Lidiane; Velasco, Fermin Garcia; Fornari Junior, Celso; Luzardo, Francisco Martínez; Tashima, Mauro Mitsuuchi [UNESP] (Elsevier, 2017)
This paper presents the results of experimental study with a new coconut fiber-cement composite (CFC). To obtain a material with improved performance in order to decrease the amount of calcium hydroxide present on the fiber surface, four forms of coconut fiber treatment were tested. Some combinations of natural latex, water and pozzolanic materials (silica fume or metakaolin) were evaluated by degradation test and accelerated aging through cycles of wetting and drying CFC samples. To determine the mechanical properties obtained from each treatment, flexural tests on CFC composites were performed. After the flexural tests, the fibers were removed from the specimens and analyzed by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), Fourier Transform Infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). The results indicate that the treatment carried out with the natural latex polymer film combined with a pozzolan layer improved the performance and durability of the CFC.
Keywords: Cement matrix; Durability; Metakaolin; Silica fume; Vegetable fibers